Connectivity between default mode and frontoparietal networks mediates the association between global amyloid‐β and episodic memory. Issue 3 (24th November 2022) - Zhukovsky, Peter; Coughlan, Gillian; Buckley, Rachel; Grady, Cheryl; Voineskos, Aristotle N.
Abstract: Βeta‐amyloid (Aβ) is a neurotoxic protein that deposits early in the pathogenesis of preclinical Alzheimer's disease. We aimed to identify network connectivity that may alter the negative effect of Aβ on cognition. Following assessment of memory performance, resting‐state fMRI, and mean cortical PET‐Aβ, a total of 364 older adults (286 with clinical dementia rating [CDR‐0], 59 with CDR‐0.5 and 19 with CDR‐1, mean age: 74.0 ± 6.4 years) from the OASIS‐3 sample were included in the analysis. Across all participants, a partial least squares regression showed that lower connectivity between posterior medial default mode and frontoparietal networks, higher within‐default mode, and higher visual–motor connectivity predict better episodic memory. These connectivities partially mediate the effect of Aβ on episodic memory. These results suggest that connectivity strength between the precuneus cortex and the superior frontal gyri may alter the negative effect of Aβ on episodic memory. In contrast, education was associated with different functional connectivity patterns. In conclusion, functional characteristics of specific brain networks may help identify amyloid‐positive individuals with a higher likelihood of memory decline, with implications for AD clinical trials. Abstract : Zhukovsky et al. show that connectivity of the posterior medial default mode network with frontoparietal areas mediates the relationship between amyloid‐beta levels and episodic memory. In contrast, education was associated with different functional connectivity patterns.